Konsep Al-Rububiyah dalam Alquran - Firdaus Firdaus (Jurnal Adabiyah: Humanities and Islamic Studies, 2011)
This writing tries to explore the deep meaning of rabb in al-Quran. The result of research found out that term of rabb in al-Quran has three meanings, namely the all creating, the all possesing, and the all arranging. It means that the term rabb refers to the substantial attribute of God. The human being’s acknowledgment of the God’s existence brings about the God consciousness that there is no God to worship but Allah. This witness leads human being to be rabbanian namely people who are strictly commited to save and keep what has become his responsibility, implement the universal values based on moral force and religious values.